Efektivitas Lembar Kerja Peserta Didik Berbasis Eksperimen Terhadap Pemahaman Konsep Titrasi - Kartini J; Kasman, Risqah Amaliah (Jurnal Pendidikan dan Pembelajaran, 2024)
Student Worksheets are student guides that are used to carry out investigation or problem solving activities. LKPD can be form of a guide to train the development of cognitive aspects or a guide to develop all aspects of learning in the form of an experimental or forced guide.The aim of this research is to identify improvements in student learning outcomes after going through the teaching and learning process using Experiment-based LKPD on acid-base titration material. This research is a quasi-experimental type research with a One Group Pretest-Posttest Design research design. The pretest and posttest results are then analyzed to identify improvements in learning outcomes. Apart from that, a t test and n-gain analysis were carried out to see the significance of this increase. The results of this analysis prove that there is a significant increase in the learning outcomes of students majoring in Fishing Ship Nauticals at SMK Negeri 2 Barru